Pengembangan Multimedia Pembelajaran Berbasis Mobile untuk Mata Pelajaran Bahasa Jawa Materi Aksara Jawa Kelas VIII SMP - Silviarista, Miranda; Setyosari, Punaji; Sihkabuden, Sihkabuden (Universitas Negeri Malang, 2017)
Abstrak: Tujuan penelitian ini adalah menghasilkan produk berupa media pembelajaran mobile mata pelajaran bahasa Jawa kelas VIII materi aksara Jawa sebagai media pembelajaran siswa secara mandiri dan memberikan visualisasi tentang materi aksara Jawa. Data dikumpulkan dengan menggunakan angket dari 1 ahli media, 1 ahli materi, dan 20 siswa dan dianalisis dengan teknik kualitatif dan kuantitatif. Hasil penelitian adalah multimedia dinyatakan valid atau layak digunakan dengan hasil perhitungan ahli media 93,45%, ahli materi 91%, kepada audiens/ siswa yaitu kelompok kecil 92,2%, dan uji coba lapangan 92,5% serta tes hasil belajar 86,7%. Kata kunci: pengembangan, media pembelajaran, mobile learning , mata pelajaran bahasa Jawa, aksara Jawa Abtract: the purpose of this research is to produce an mobile learning product for Javanese subject of eight grade which the main topic is aksara Jawa which as individual learning and to give visualization about aksara Jawa materials. The data are collected by using questionaire from 1 expert of media, 1 expert of the subject material, and 20 of students and it is analysed by qualitative and quantitative technique. The resultt of this research is the multimedia is validly asserted or suitable to be used based on the counting result of the media expert 93,45%, subject material expert 89,28%, to audiences/students which is individual 82,05%,a small group 82,378%, and the experiment in the field 82,88%, learning result test 86,7%.Abstract: The purpose of this study was to produce a product in the form of mobile learning media in Javanese language subjects in class VIII Javanese script material as a medium for student learning independently and provide visualization of Javanese script material. Data was collected using a questionnaire from 1 media expert, 1 material expert, and 20 students and analyzed by qualitative and quantitative techniques. The results of the study were multimedia declared valid or feasible to be used with the results of the calculation of media experts 93.45%, material experts 91%, to the audience/students namely small groups 92.2%, and 92.5% field trials and test results 86, 7%. Keywords: development, learning media, mobile learning, Javanese language subjects, Javanese script subject of eight grade which the main topic is Javanese script which as individual learning and to give visualization about Javanese characters. The data were collected by questionnaire from 1 expert of media, 1 expert of subject matter, and 20 students and analyzed by qualitative and quantitative techniques. The result of this research is that the media is validly asserted to be used based on the counting result of the expert media 93.45%, the subject matter expert is 89.28%, to audiences/students which is individual 82.05%, a small group 82.378%, and the experiment in the field 82.88%, the learning result test is 86.7%.